2016
DOI: 10.1111/1750-3841.13434
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor, Antioxidant, and Nitrite Scavenging Effects of Chinese Water Chestnut (Eleocharis dulcis) Peel Flavonoids

Abstract: The preparation, quantification, and characterization of flavonoid compounds from Chinese water chestnut peel (CWCP) flavonoid extract and ethyl acetate fraction (EF), n-butanol fraction, and water fraction were studied. Among these, EF showed the maximum free radical levels (IC values of 0.36, 0.40, and 0.37 mg/mL for DPPH•, ABTS• , and •OH, respectively), nitrite scavenging effects (IC = 1.89 mg/mL), and A549 cell inhibitory activities (IC = 776.12 μg/mL) with the highest value of total flavonoid content (TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 44 publications
0
31
0
1
Order By: Relevance
“…The result from Androutsopoulos et al suggested that DIO induces anticancer activity in MCF7 breast cancer cells by causing cytochrome P450 bioactivation [13]. Meanwhile, Zhan et al found that DIO could induce G1/S arrest and cell apoptosis in human lung cancer A549 cells [14]. However, no reports have been published to test agent DIO as a radiosensitizer to improve radiosensitivity so far.…”
Section: Introductionmentioning
confidence: 99%
“…The result from Androutsopoulos et al suggested that DIO induces anticancer activity in MCF7 breast cancer cells by causing cytochrome P450 bioactivation [13]. Meanwhile, Zhan et al found that DIO could induce G1/S arrest and cell apoptosis in human lung cancer A549 cells [14]. However, no reports have been published to test agent DIO as a radiosensitizer to improve radiosensitivity so far.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, FL also restored activities of both superoxide dismutase (SOD) and catalase (CAT) in the liver to normal status, which allopurinol failed to [ 16 ]. Chinese water chestnut ( Eleocharis dulcis ), one of the favorite foods in Asia due to its unique taste, can be used as a folk medicine to treat hypertension, chronic nephritis, constipation, and pharyngitis [ 17 ]. The peel that is discarded as a by-product during the processing of Chinese water chestnut, constitutes approximately 20% (w/w) of the whole fruit, so the recycle of the Chinese water chestnut peel (CWCP) is beneficial to the environment and economy [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese water chestnut ( Eleocharis dulcis ), one of the favorite foods in Asia due to its unique taste, can be used as a folk medicine to treat hypertension, chronic nephritis, constipation, and pharyngitis [ 17 ]. The peel that is discarded as a by-product during the processing of Chinese water chestnut, constitutes approximately 20% (w/w) of the whole fruit, so the recycle of the Chinese water chestnut peel (CWCP) is beneficial to the environment and economy [ 17 ]. Previous studies on the activity of CWCP have shown that its flavonoids have antioxidant, anticancer, antibacterial and nitrite scavenging functions [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This plant is a widespread species native to fresh-water or brackish marshes of the old world tropics from adagascar to India, south-eastern Asia, the Philippines, Malaya, Indonesia, Melanesia and Fiji [1][2] . In China, It is estimated that the annual production of E. tuberosa was about 900,000 tons in 2015 [3] . The fruits of water chestnuts contain high starch levels and are most often eaten after boiling or are used as sources of alcohol [4] .…”
Section: Introductionmentioning
confidence: 99%
“…E. tuberosa has also been used as a folk medicine to treat hypertension, chronic nephritis, constipation, pharyngitis, laryngitis and enteritis [6][7] . In recent years, fresh-cut E. tuberosa corms are in high demand because of their unique taste and medicinal properties [3] . A large number of peels were wasted.…”
Section: Introductionmentioning
confidence: 99%